Assesing Customer Acceptance Toward Intention to Use e-Toll Card Using Technology Acceptance Model (TAM) - Nurantono, Fauzi Gunawan (Journal of Business and Management, 2017)
Abstrac. At this time, the utilization of Electronic payment has become one of the most frequently used as the payment method. Electronic payment give the benefit of ease and convenience transaction for the customer. In Indonesia, cashless payment reach into 31% from all consumer method and Indonesia classified as the country just begun to move into electronic money. This condition supported by government policy to diminish cash transaction by using electronic payment. Electronic Toll Card as the product of electronic payment applied in transportation sector. However, at this time, most of toll road user still use cash payment.Â The purpose of this research is to assessing the toll road user acceptance toward intention to use of electronic toll card. The consumer acceptance is important aspect to make the consumer using the product. In this research, Technology Acceptance Model use as the research framework to understand consumer acceptance. The research was using 5 main construct including self-efficacy, perceive usefulness, perceive ease of use, attitude toward use, and intention to use. The construct was based on the previous research of TAM and electronic payment.Â The results of this research shows all of the variables are significant relationship between each of variable with significant value is 0.000. Perceive usefulness is strongest variable to affect intention to use which account 0.598.Keywords: Consumer behavior, Intention to use, Technology Acceptance Model.